Washington and Essex Streets intersection, ca. 1900 - Unknown (Tufts Archival Research Center, 2005)
Street-level view northeast of the Washington and Essex Streets intersection. (Left to right) 590-622 Washington Street, located between Essex Street to the south and Hayward Place to the north, are included in the left half of the photograph, while 16-42 Essex Street are included in the right half of the photograph. Signage and awnings adorn most of the buildings, and electricity lines cross the street intersection. Street railroad tracks and horse-drawn vehicles fill both Washington and Essex Streets, and pedestrians are included in the photograph. 6 1/4 x 8 1/8, 6 1/2 x 8 7/16 overall Photographs